LENGUAJE Y TEOLOGÍA EN EL TERCER CONCILIO DE TOLEDO - González Blanco, Antonino (Antigüedad y Cristianismo, 1995)
This study starts with the analysis of the language of the Council, which was carried out by means of the informatization of the Acts and the elaboration of concordances. An intent is made to capture the message given in the texts of the Council, and a reflexion is made on the concepts: Church, Bishop, Faith, God's People and Sacredness. The study ends with reflexion on the language and the theology used in the Council. (...)